Strategi Pengembangan Rumah Baca Asma Nadia Sumbang - Isnaini - Nurisusilawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
Asma Nadia is a reading house at Sumbang Subdistrict, Banyumas Regency, Central Java which started on May 26th , 2016. There were nine volunteers at the reading house. The objective of reading house was to increase reading interest and build mental character especially for children. In fact, the reading interest was high but it was not supported with adequate reading house facilities. The limited reading space in reading house made them to shift another area. In addition, the collection of books was limited as well. In terms of library management, there were many unrecorded and unclassified books and ability of volunteers to use information technology were relatively low. Morover, In terms of funding, there had been several efforts made by volunteers such as selling drinks or making paper flower but those were undeveloped well. So, by those problems, some programs had been created such as training Senayan Library Management System (SLIMS) software, classifying and labelling books, holding on e-commerce business communication strategies workshop and children writing competition. The generated outcome from the internal community activities were implemented for library information systems, publications on ISSN community service of scientific journal, and online publication.